Pre-pregnancy maternal obesity in Greece: A case–control analysis. (February 2016) - Papachatzi, E.; Paparrodopoulos, S.; Papadopoulos, V.; Dimitriou, G.; Vantarakis, A.
Abstract: Background—aims: Pre-pregnancy obesity may cause significant health implications for both mother and neonate. Our study aims to investigate the association between pre-pregnancy Body Mass Index and the risk for cesarean section, admission to Neonatal Intensive Care Unit, macrosomia and preterm delivery, in a Mediterranean country. Study design: A matched retrospective case control analysis was conducted. Subjects: The study population included all pregnant women (with known Body Mass Index data) who gave birth in the University Hospital of Patras between 1st of January 2003 and 31st of December 2008. Outcome measures: Cases were defined as obese (338) or overweight (826) women. Results: Overweight and obese women were at higher risk for cesarean section, NICU admission and preterm delivery (χ 2 (2) = 36.877, p < 0.001, χ 2 Imes and Burke (2014) = 6.586, p = 0.037 and χ 2 Imes and Burke (2014) = 7.227, p = 0.027 respectively). Neonatal mean birthweight was higher among obese and overweight women ( p < 0.0001). Conclusions: Both obese and overweight pregnancies should be considered as high risk pregnancies, due to more frequent adverse pregnancy outcomes (cesarean delivery, preterm delivery and NICU admission). Highlights: Obesity has been correlated to adverse pregnancy outcomes such as gestational diabetes, preeclampsia, preterm delivery and cesarean delivery. Neonates born to obese women are at increased risk for macrosomia, low Apgar scores and Neonatal Intensive Care Unit admission. We evaluated the association between pre-pregnancy maternal obesity and the risk for cesarean section, admission to Neonatal Intensive Care Unit, macrosomia and preterm delivery in a Mediterranean population. Obesity is an independent risk factor for adverse pregnancy outcomes (cesarean section, NICU admission, macrosomia and preterm delivery) There is also a high risk, towards adverse pregnancy outcomes, for the overweight women too.